Challenges Faced by English Education Students in Mastering Vocabulary Through Online Learning Systems - Sadewi, Ni Ketut Asta Denny; Mahardika, I Gusti Ngurah Agung Wijaya; Mahendra, Made Wahyu (FKIP - Universitas Tanjungpura, 2024)
Vocabulary is the primary skill EFL students need to speak English fluently. It is not as simple as one may think of learning English vocabulary by simply recalling words